Community-supported agriculture as food democratic experimentalism: Insights from Germany - Degens, Philipp; Lapschieß, Lukas (Frontiers in Sustainable Food Systems, 2023)
This paper analyzes community-supported agriculture (CSA) as a particular form of democratic experimentalism in food systems. Specifically, we explore both primary and secondary CSA initiatives in Germany, based on participatory observation on meetings and workshops, and on qualitative interviews. Opposing the industrial food system and market-based food distribution, CSA activists envision transformative change toward a sustainable, regionalized, and more democratic food system. A key feature of CSA as a specific form of alternative food organizations is its underlying collaborative effort among farmers and households: consumers take over production risks, make investments in their CSA and share crops, whereby they decouple producers' income from harvest yield and market prices. Employing a perspective that is informed by John Dewey's notion of democratic publics and experimentalism, we show that both on the primary and secondary levels as well as in collaboration with other political, economic, or civic actors, CSA is a manifestation of civil society's ongoing and never-ending inquiry to find joint solutions for their shared problems. We explore CSAs as democratic forms, in terms of their diverse internal structures and practices within the primary initiatives and also the secondary network. Furthermore, we reflect on their overall potential to democratize food systems. On all levels, we find the modus of experimentalism as the essential form of democratic inquiry. We show how the varying kinds of democracy that are embodied by primary initiatives differ from one another, and what kind of boundaries exist. These boundaries, inter alia, limit CSA's potential to achieve food democracy on a societal level, if democracy means giving everyone the opportunity to have a say whenever they are affected.